Cascaded valorization of seaweed using microbial cell factories. (October 2020) - Poblete-Castro, Ignacio; Hoffmann, Sarah-Lisa; Becker, Judith; Wittmann, Christoph
Graphical abstract: Highlights: Seaweed represents an important future biorefinery feedstock. The world market has reached more than 30 million tonnes per year. Cascaded valorization provides food, feed, functional materials, chemicals and energy. Metabolic engineered cell factories can convert seaweed sugars into novel products. Abstract : Sustainable production from seaweed has grown into an area of intense research and development. Meanwhile, more than 30 million tonnes of seaweed are produced, of which 70% are used as food and 30% have other applications such as feed, fertilizer, chemicals, and energy. Towards biorefining seaweed in an environmentally friendly and economically viable manner, we need efficient approaches that convert its biomass and residuals into added value products. Smart cell factories and fermentation strategies which can be integrated into future seaweed biorefineries are at the heart of the development and therefore receive increasing attention. Here, we review advances in the field including novel fermentation routes from seaweed to chemicals, materials, pharmaceuticals, fuels and energy, and discuss challenges and opportunities.